PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, DAN PRAKTIK CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Riske Meitha Anggraeni; Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2013)
This  study  aims  to  examine  managerial ownership structure, firm size, and corporate  governance  on earnings management. Earning management was measure by discretionary accruals, ownership managerial structure was measure by the percentage stock of managerial,  firms size was measure by natural logaritma of total asset, and corporate governance were measure by three variabels (composition of board commissioner independent, total of audit committee, and KAP size big 4 or non big 4). This study used data of 111 manufacturing companies listed in BEI from 2009- 2011 . Methods of data collection used  purposive  sampling  techniques. The data were then analized using multiple regression analysisThe  results  shows  that  the  managerial ownership structure and firm size size has  no  significant  effect  on  earnings  management.  Meanwhile, the Corporate Governance (composition of board independent commissioners, audit committee, and KAP size) have significant effect on earning management.